Nursing Students' Perceptions on Healthcare-Associated Infection Control and Prevention Teaching and Learning Experience: Development and Validation of a Scale in Four European Countries - Yurrebaso Macho, Amaia; Ward Mayens, Alexander L.; Picado Valverde, Eva Ma; Guzmán Ordaz, Raquel; Juanes Méndez, Juan Antonio; Pérez Iglesias, Jose Luis; Mirón Canelo, José Antonio; Pinto, Maria do Rosário; Costa Reis, Alcinda Maria do Sacramento; Simões, Joaquim Augusto; Torres, Ana Luísa; Silén-Lipponen, Marja; et al. (Frontiers in Psychology, 2021)
Healthcare-associated infections are one of the major concerns worldwide. This study presents the development and the validation process of the InovSafeCare scale, aimed at identifying and measuring the ecosystem variables related to Healthcare-associated Infection (HCAI) prevention and control practices in European nurse students. Qualitative and quantitative approaches were used to 1) elaborate an item pool related to the educational environment, the healthcare setting environment, and the attitudes, beliefs, and performance of the nursing students regarding healthcare-associated infections prevention and control; and 2) analyze psychometric properties of the scale using factor analysis. The validated InovSafeCare scale was applied to undergraduate nursing students of five European Higher Education Institutions. The Partial Least Square Structural Equation Modeling (PLS-SEM) method with SMART-PLS3 software was used. The study sample consists of 657 nursing students, who responded a self-report inventory. From the analyzed data were identified fourteen factors. The InovSafeCare scale reveals good validity and reliability of the dimensions in different European countries.